Pengaruh Sosial Media Marketing dan Kualitas Pelayanan terhadap Keputusan Pembelian Melalui Minat Beli Konsumen sebagai Variabel Intervening pada Toko Liza Kosmetik Padang - Anisah Fitria Efendi; Vicky Brama Kumbara; Emil Salim (JURNAL RISET MANAJEMEN (JURMA), 2025)
This research aims to determine and try to analyze the influence of social media marketing and service quality on purchasing decisions through purchase interest at the Liza Cosmetics Padang store. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample for this study were visitors to the Liza Cosmetics Padang shop. The research results found that there is an influence between Social Media Marketing on Purchase Interest. There is an influence between Service Quality on Purchase Intention. There is an influence between Social Media Marketing on Purchasing Decisions. There is no influence between Service Quality on Purchasing Decisions. There is an influence between Purchase Interest and Purchase Decisions. Purchase Interest mediates Social Media Marketing on Purchase Decisions. Purchase Interest mediates Service Quality on Purchase Decisions.